Alexandre Rodrigues Ferreira e seus estudos das plantas do norte e centro-oeste do Brasil - Oliveira, Patrícia Paula de (2009)
The subject of this dissertation is the study of plants carried on by Alexandre Rodrigues Ferreira (1756-1815) during his journey to Rio Negro between 1783 and 1786. The objectives were to gather plants references contained in the trip diaries, as well as in botanic memories written by the author, in the attempt to establish the disciplinary record that guided the naturalist s look. The first chapter brings the biographical aspects of Alexandre Rodrigues Ferreira, his graduation at Coimbra, his planning for the philosophical journey in the context of the introduction of modern science in Portugal, as well as the destination given to the naturalist´s work. The second chapter discourses upon the History of Botany with the purpose of situating the reader in the scientific context in which the naturalist was in, namely the XVIIIth Century s Portugal. In this same chapter is made an analysis of the minor botany memories left by the naturalist. The third chapter brings a discussion supported by information we gathered from plants references made by Alexandre Ferreira in his Diary of the Philosophical Journey to Rio Negro. At the end, in our Final Considerations, we present the conclusions based on the results achieved in our analysis. Along our research we identified the aspects referred by the naturalist to describe the plants according to several disciplinary records. The methodology used consisted in marking all Alexandre Rodrigues Ferreira references about plants and indicate which current knowledge context we believe they fit in. We found Alexandre Rodrigues Ferreira references to plants according to the following areas and subareas: Botany (morphology, physiology, and identification), Agriculture (food, planting, economy/production, and general comments), Medicine (medicinal plants) and General (food, drinks, construction, furniture, objects, clothing, textile, dye, no cultivated plants, conservation and general comments). Our research allowed us to identify this mix of approaches, bringing into attention, quantitatively, the agricultural focus. In our opinion, Alexandre´s records were according to his background at Coimbra University, as well as in tune with the botanical production of the period